Characterization pH, stability of emulsion, and viscosity canola oil (Brassicca napus L.) emulsion (O/W). Issue 1 (October 2020) - Putra, A M; Syarifuddin, A; Dirpan, A
Abstract: The aimed of this research was to determine the best oil in water emulsion as the main ingredient in the gel matrix. The experimental design of this study used a factorial completely randomized design with two factors. The factors were factor canola oil concentration using 30%(CO1), 40%(CO2), and factor xhantan gum concentration using 0.3%(XG1), 0.5%(XG2). The best emulsion formulation was selected based on functional properties such as pH, emulsion stability and viscosity. The result of research showed that the using of 40%(CO2) canola oil concentration and 0.5%(XG2) xhantan gum had the best oil in water (O/W) emulsion. This was indicated by the results of pH 6, 5, the highest emulsion measurements (99.4%) and viscosity (22226 cP). canola oil concentration affects the pH value of the emulsion, the stability of the emulsion and viscosity are influenced by the concentration of xhantan gum and the concentration of canola oil. the higher the concentration of xhantan gum, the higher the stability of the emulsion and viscosity.